During Development NG2 Glial Cells of the Spinal Cord are Restricted to the Oligodendrocyte Lineage, but Generate Astrocytes upon Acute Injury. (10th August 2018) - Huang, Wenhui; Bai, Xianshu; Stopper, Laura; Catalin, Bogdan; Cartarozzi, Luciana Politti; Scheller, Anja; Kirchhoff, Frank
Graphical abstract: Highlights: Developing spinal cord NG2 glia stay within the oligodendrocyte lineage and do not generate astrocytes or neurons. The differentiation to mature oligodendrocytes occurs in an age- and region-dependent manner. Acute spinal cord injury can trigger spinal NG2 glia to generate astrocytes in both, gray and white matter. Abstract: NG2 glia are self-renewal cells widely populating the entire central nervous system (CNS). The differentiation potential of NG2 glia in the brain has been systematically studied. However, the fate of NG2 glia in the spinal cord during development and after injury is still unclear. Here, we took advantage of faithful expression of Cre in NG2-CreERT2 knock-in mice to demonstrate that spinal NG2 glia remain committed to the oligodendrocyte (OL) lineage and generate OLs, but not astrocytes or neurons, during development. However, we found significant age- and region dependent differences in differentiation into OLs. Embryonic or neonatal NG2 glia generated more than 90% of the white matter OLs, but only 50% (embryonic) or 75% (neonatal) of gray matter OLs. Such differences disappeared after myelin completion coinciding with a decrease in the differentiation rate. While we never detected the generation of astrocytes from NG2 glia during spinal cord development, we found a small portion of NG2 glia could generate astrocytes in adult spinal cord upon acute traumatic injury.